Measuring the capacity utilization of China's transportation industry under environmental constraints. (August 2020) - Zhang, Jingxiao; Cai, Wenyi; Philbin, Simon P.; Li, Hui; Lu, Qing-Chang; Ballesteros-Pérez, Pablo; Yang, Guo-liang
Highlights: Measuring the capacity utilization of China's transportation industry in 2011-2017. Adding a link between variables can improve the accuracy of the measurement results. China's transportation industry faces the issue of underutilization of capacity. Better transportation resources planning can improve the capacity utilization level. Abstract: The transportation industry is challenged by the need for capacity optimization, energy saving and decreasing emissions. Improving our understanding of capacity utilization is important for achieving a strong transportation system. This article analyzes the relationship between carbon dioxide emissions and final energy consumption in the transportation industry. The capacity utilization of China's transportation industry in the period 2011–2017 is explored by two improved DEA-based difference methods. They assess the status quo of China's capacity utilization and explores effective mechanisms to increase it. In addition, the rationale and accuracy of both measurement models are analyzed. Results show that: (1) the relationship between CO2 emissions and final energy consumption can be taken advantage of to improve the accuracy of capacity utilization measurements. (2) China's transportation industry has suffered from the underutilization of capacity, especially in the past three years. (3) Regional differences in capacity utilization are significant, being Southwestern China the region that has most seriously underutilized its capacity. (4) Promoting transportation technology innovation and more rational transportation resources planning are two key mechanisms to improve capacity utilization. This paper broadens our research knowledge of the transportation industry by proposing new measurement approaches for capacity utilization. These can be used to implement more effective and targeted policies, better allocate production resources, and closely monitor capacity utilization.